Optimasi Pelayanan Pelanggan: Suatu Penelitian Analisis Kualitas Layanan - Nafisah, Dewi; Surianto, Moh. Agung (El-Idare, 2024)
This research aims to optimize customer service through the analysis of service quality using a qualitative approach. Through the collection of descriptive data in the form of written and oral language from observable respondents, the study seeks to delve into individual or group phenomena related to customer service. The research methodology adopts the Miles and Huberman model with a focus on data presentation, data reduction, and conclusion drawing. The results of this data analysis are expected to provide a complex overview of customer service quality, identify weaknesses or deficiencies that may exist, and provide a basis for improvement recommendations. This research contributes to understanding customer expectations and perceptions, advancing the understanding of customer service in the context of modern business, and providing a foundation for company strategies to achieve a competitive advantage through superior customer service.